Kepemimpinan Primal; Studi Pada Kepemimpinan Perusahaaan Pelayaran PT. MK Semarang - andi hendrawan; Hari Sucahyowati; Indriyani Indriyani (Sekolah Tinggi Maritim Yogyakarta, 2021)
The role of leadership is very strategic and important for achieving the mission, vision and goals of an organization, primal leadership is leadership based on emotional intelligence, it is hoped that primal leadership is a type of leadership that will improve the performance and welfare of society. This study aims to describe the primal leadership at PT MK Semarang. This research is both qualitative and quantitative by taking a sample of 30 employees of PT MK. The results of the research show that primal leadership is in a good category, even for the competency dimension of the category relationship is very good.